Managerialism: A workforce health hazard in human service settings. Issue 8 (26th May 2022) - Zelnick, Jennifer R.; Abramovitz, Mimi; Pirutinsky, Steven
Abstract: Background: This study assesses the relationship between managerialism and health among human service workers. Methods: A total of 2154 New York City human service workers participated in an electronic survey that included validated measures of a system of work organization (the Organizational Commitment to Managerialism scale [OCTM]) and a work stressor (the Effort Reward Imbalance scale [ERI]), and single items about physical, mental, and behavioral health. Controlling for demographic variables, logistic regression models were used to predict health outcomes assess the potential role of ERI as a mediator. Results: Managerialism was associated with increased risk of high blood pressure, neck and back pain, gastrointestinal difficulties, sleeping disorders, anxiety, and depression. Mediation analyses suggested that the effects of managerialism on health were partially explained by ERI. Conclusions: Managerialism in human service agencies significantly increased the risk of adverse physical and mental health. Increased levels of a work stressor helped to explain part of this association.